Programable ac power control / Muhammad Amirul Idham Laili & Megat Amir Hanafi Megat Taftazani - Laili, Muhammad Amirul Idham; Megat Taftazani, Megat Amir Hanafi (2015)
The project is designed to see the effect of the firing angle of the transistor to the load power. Based on the principle of firing angle control of thyristors, one can control the ac power. A display unit displays the full power or any percentage and one can enter the desired percentage to reduce the power to the load. The firing angle would be automatically adjusted to maintain the load power. The project uses a lamp such that the entered power matches the required one.